Efficacy of fractional CO2 laser combined with 5-aminolevulinic acid photodynamic therapy on actinic keratosis in face - Ming WANG; Xin TIAN; Yuan LU; Xia WANG; Ping ZHONG; Bao CHAI; Peng WANG; Chunyan HUANG; Changzheng HUANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To observe clinical effects and safety of fractional CO2 laser combined with 5-aminolevulinic acid photodynamic therapy (ALA-PDT) on facial actine keratosis (AK). Methods 15 cases of facial actine keratosis were given fractional CO2 laser combined with 5-ALA-PDT in the open and uncontrolled clinical study, for 1~5 times, followed up for 12 months. Results Two patients achieved complete remission after once treatment, 4 cases achieved complete remission after twice treatments, and 9 cases achieved complete remission after three to five times treatments. There was no recurrence after 12 months of follow-up. 3 cases reported excellent cosmetic effect, 7 cases reported good cosmetic effect, and 5 cases reported average cosmetic effect. During the treatment, 11 cases of the patients had slight pain, 4 cases had obvious pain. Conclusion Fractional CO2 laser combined with 5-aminolevulinic acid photodynamic therapy on facial actine keratosis is a safe, cosmetic and effective treatment.